2008
DOI: 10.2460/ajvr.69.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acepromazine, butorphanol, or N-butylscopolammonium bromide on visceral and somatic nociception and duodenal motility in conscious horses

Abstract: Each drug caused predictable changes in sedation and vital signs, but consistent anti-nociceptive effects were not evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 34 publications
2
47
0
1
Order By: Relevance
“…However, Grint and others (2014) reported mean MNT values of 9.2 N using a rate of application of force of 0.4 N/second in donkeys. The difference in basal MNT values between studies may be due to the use of different actuators as it has been demonstrated in horses (Taylor and others 2012). …”
Section: Discussionmentioning
confidence: 99%
“…However, Grint and others (2014) reported mean MNT values of 9.2 N using a rate of application of force of 0.4 N/second in donkeys. The difference in basal MNT values between studies may be due to the use of different actuators as it has been demonstrated in horses (Taylor and others 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that affected horses experienced some degree of analgesia thus continued to eat hay despite developing ileus, until a more severe problem developed. In prior studies, we were unable to demonstrate visceral anti-nociceptive effects with lidocaine [10] or butorphanol [13] administered as a CRI to healthy horses. It is not known whether anti-nociceptive properties would exist with this drug combination in ill or painful horses.…”
Section: Discussionmentioning
confidence: 99%
“…This supports prior work in healthy horses [20] and horses post-celiotomy [14], which also showed decreased fecal output. But, in healthy horses, a short duration butorphanol CRI did not significantly alter duodenal motility [13]. The observed decrease in fecal weight and prolonged passage of beads for combinations that included butorphanol may be due to numerous factors including the potential for accumulation of any drug or its metabolites during the infusion, competitive metabolism, or a potential synergistic inhibitory effect on motility of drugs given in combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sanchez et al 17 the dose of 18 µg kg -1 , but not after infusion at the rate of 13 µg kg -1 hour -1 for 2 hours. The same observations were reported by Sellon et al 8 using doses of 0.13 mg kg -1 as a bolus, followed by a continuous rate infusion of 13 µg kg -1 hour -1 for 24 hours.…”
Section: Discussionmentioning
confidence: 99%